Kebudayaan Indis sebagai Warisan Budaya Era Kolonial - Gultom, Adam Zaki (Warisan: Journal of History and Cultural Heritage, 2020)
Indies culture is a reflection of the lifestyle patterns adopted by a small part of the inhabitants of the archipelago in the colonial period. The Indies lifestyle experienced a glorious period until the beginning of the 20th century. Supporters of Indies culture were not only Dutch, but the indigenous elite group had also entered the Indies' cultural circle. The background to the emergence of Indies culture began with the presence of the Dutch in the Archipelago. The presence of the Dutch caused a meeting of two cultures, namely Western and Eastern cultures, which gave rise to a new culture, namely the Indies culture. At the beginning of its development, cultural change became a mixture of Dutch and Javanese. Channels of the development of Indies culture influenced housing, art, science, and religion. Today's culture can still be seen from colonial buildings, birth ceremonies, marriages, and deaths.Keywords: Indies culture, culture acculturation, colonial heritage.